Comparison between First- and Second-Generation Cryoballoon for Paroxysmal Atrial Fibrillation Ablation. (16th March 2016) - Conti, Sergio; Moltrasio, Massimo; Fassini, Gaetano; Tundo, Fabrizio; Riva, Stefania; Dello Russo, Antonio; Casella, Michela; Majocchi, Benedetta; Marino, Vittoria; De Iuliis, Pasquale; Catto, Valentina; Pala, Salvatore; et al.
Abstract : Introduction . Cryoballoon (CB) ablation has emerged as a novel treatment for pulmonary vein isolation (PVI) for patients with paroxysmal atrial fibrillation (PAF). The second-generation Arctic Front Advance (ADV) was redesigned with technical modifications aiming at procedural and outcome improvements. We aimed to compare the efficacy of the two different technologies over a long-term follow-up. Methods . A total of 120 patients with PAF were enrolled. Sixty patients underwent PVI using the first-generation CB and 60 patients with the ADV catheter. All patients were evaluated over a follow-up period of 2 years. Results . There were no significant differences between the two groups of patients. Procedures performed with the first-generation CB showed longer fluoroscopy time (36.3 ± 16.8 versus14.2 ± 13.5 min, resp.;p = 0.00016 ) and longer procedure times as well (153.1 ± 32 versus102 ± 24.8 min, resp.;p = 0.019 ). The overall long-term success was significantly different between the two groups (68.3 versus 86.7%, resp.;p = 0.017 ). No differences were found in the lesion areas of left and right PV between the two groups (resp., p = 0.61 and0.57 ). There were no significant differences in procedural-related complications. Conclusion . The ADV catheter compared to the first-generation balloon allows obtaining a significantly higher success rate after a single PVI procedure during the long-term follow-up. Fluoroscopy and procedural times were significantly shortened using the ADV catheter.